Psychological effects and coping strategies after major surgery in adults - Divaasini Devaraj; Zhooriyati Sehu Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2019)
This qualitative phenomenological was conducted to explore the psychological experiences and coping strategies utilized by surgical patients who developed psychological effects after major surgery. To meet the objectives of this study, five participants aged between 45 to 63 years old were recruited though purposive and snowball sampling across Klang Valley, Malaysia. The participants who underwent various major surgeries (Hemicolectomy, Craniotomy, Mastectomy, total knee replacement, and brain aneurysm repair) were interviewed using semi-structured questions on different days and places. Thematic Analysis was used to analyze the data gathered through the interviews with participants. This research found that individuals who undergo major surgeries display strong dependency on their families, anxiety about hospital and illness, negative emotional experiences, insecurity and isolation towards society as well as dissatisfaction due to lifestyle changes. To overcome the psychological effects faced after major surgery, this study found that adults utilize adaptive coping strategies such as seeking for social and professional help, practicing selfmanagement, spirituality and optimism as well as giving and receiving support from loved ones. Through the findings of this research, awareness regarding familial role towards postsurgery recovery can be increased and steps such as introducing psychological screening for surgical patients could be implemented in Malaysia.